An accurate interband tunneling model for InAs/GaSb heterostructure devices. Issue 5 (6th February 2013) - Shams, Md. Itrat Bin; Xie, Yi; Lu, Yeqing; Fay, Patrick; Krishna, Sanjay; Plis, Elena
Abstract A numerical model that accurately describes interband tunneling in backward diodes and broken‐gap tunnel diode structures based on the InAs/GaSb material system is described. The model applies the transfer matrix method to discretized bias‐dependent energy band profiles to calculate the transmission probability for tunneling. The model has been validated against experimental results, with good agreement in the current‐voltage and curvature coefficient having been obtained for a range of hetero‐structure backward diode and interband tunnel diode structures. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)